Effect of Dry Extracts of Medicinal Plants on Urinary Excretion and Ion Exchange - G. Yu., Djanaev; Sh. M., Makhsumov; O. A., Zaytseva; Kh. I., Khudayberdiev; O. O., Askarov (Journal of Medical Genetics and Clinical Biology, 2024)
According to the results of an experimental scientific study, in relatively small doses of dry extracts of the studied plants (100 μg/kg + 50 mg/kg), the average urinary excretion was 61.9% compared to the control group, and in large doses (250 μg + 100 mg/kg) was found to increase by 73.8%. Therefore, when plant extracts are used in the studied doses, their effect on urine excretion remains at full blood level.